Flow induced vibration of two rigidly connected circular cylinders in different arrangements at a low Reynolds number. (1st December 2020) - Gao, Yun; Yang, Bin; Zhu, Hongjun; Peng, Geng; Zhang, Zhuangzhuang; Pan, Ganghui
Abstract: The flow induced vibration (FIV) responses of two rigidly connected cylinders in various arrangements have been studied numerically using the two-dimensional incompressible Navier-Stokes equations coupling with a fourth-order Runge-Kutta method. Four different values of the angle of incidence ( α ) and two different values of center-to-center pitch ( P ) between the two cylinders have been selected for the study. The FIV response amplitudes, lock-in regions, hydrodynamic force coefficients, phase portraits, and flow fields have been systematically compared. The numerical results demonstrate that for P = 4 D and increasing α, the maximum value of the total mean drag coefficient tentatively increases, however, the maximum response amplitude shows a decreasing tendency. Furthermore, the maximum amplitude for P = 4 D occurs when α = 0° at V r = 7. For P = 4 D and α = 0°, the response amplitude remains a certain value during the large V r range, which is caused by the participation of the wake-induced vibration. For P = 2 D, the maximum amplitude happens when α = 30° at V r = 12. For P = 2 D when α = 90°, owing to the proximity-induced galloping, during the large V r range, the response amplitude increases slightly with increased V r, displaying no desynchronization characteristics. Highlights: The response amplitudes and lock-in regions of the two rigidly connected cylinders were studied. The hydrodynamic force coefficients of the two rigidly connected cylinders were further studied. The detailed information of the flow fields behind the two rigidly connected cylinders were examined.